EVALUATION OF QUALITY OF POULTRY FEEDS SOLD IN KATSINA METROPOLIS, KATSINA STATE, NIGERIA (FUDMA JOURNAL OF SCIENCES, 2021)
In Katsina metropolitan, a variety of poultry feeds are available, and the quality and standards of these feeds are critical for the production of eggs and meat. As a result, the quality of selected chicken feeds sold in Katsina metropolitan was assessed by performing proximate analysis using AOAC methodology. Super starter, grower concentrate, broiler finisher, broiler starter, broiler super starter, layer mesh, grower mesh, and layer concentrate were among the samples used. The percentage mean to standard deviation was used to express the findings. The crude protein content of the diets studied ranged from 0.46 ± 0.00 percent to, 8.24± 0.02 percent, ash content 6.31± 0.01 percent – 33.30± 0.04 percent, crude fiber content 1.03 ±0.00 percent – 3.21± 0.00 percent, lipid content 0.11± 0.00 percent, 2.30 ±0.00 percent, moisture content 4.28 ±0.25 – 6.66 ±0.78 percent, and carbohydrate content 51.78± 2.68 – 83.72 ±0.57 percent. Although there was variation in the mean and standard deviation levels among the samples analyzed, such variations were not statistically significant (P>0.05) according to a one-way analysis of variance (ANOVA) for the difference in the mean levels of parameters evaluated in eight samples
Keywords: Poultry Feeds, Proximate Analysis, Katsina Metropolis